Biological activity of Annona muricata seed extracts - Hoe, Pik Kheng; Yiu, Pang Hung; Ee, Gwendoline Cheng Lian; Wong, S. C.; Amarthalingam, Rajan; Bong, Joseph Choon Fah (University of Malaya, 2010)
A study was conducted to assess the biological activity of Annona muricata hexane, methanol and chloroform seed extracts. Both the hexane and methanol extracts showed moderate larvicidal activity against the Aedes aegypti larvae while the chloroform extract exhibited strong larvicidal property with an LC50 value of 0.9005µg/ml and an LC90 value of 6.1776µg/ml. Fraction 44b and 45b of the chloroform extracts were very toxic towards mosquito larvae with LC50 values of 0.7460 and 1.0402µg/ml, respectively. Identification of bioactive compounds revealed the presence of solamin, an acetogenin. From the cytotoxic assay against brine shrimp (Artemia salina), the methanol extract showed high toxicity with an LC50 value of 11.8823µg/ml. The results suggest potential application of the extracts in insecticidal formulations.